2022
DOI: 10.1007/s10461-022-03594-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-World User Experiences with a Digital Pill System to Measure PrEP Adherence: Perspectives from MSM with Substance Use

Abstract: Once-daily oral pre-exposure prophylaxis (PrEP) is highly effective for preventing HIV transmission, but adherence can be challenging for men who have sex with men (MSM) who use substances. A novel method for directly measuring ingestion events is a digital pill system (DPS), which comprises an ingestible radiofrequency emitter that signals a wearable Reader device upon PrEP ingestion, relaying ingestion data to a wearable Reader device and then to a smartphone application. Qualitative interviews were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Previous pilot data from individuals with TB using ingestible sensor systems for ATT in the United States demonstrate high patient acceptance of the system and a desire to remain on DPS-based ATT adherence monitoring compared to DOT [ 16 ]. These sentiments mirror our previous work in HIV pre-exposure chemoprophylaxis that demonstrates high patient acceptance of these systems [ 24 26 ]. We anticipate that prior to deployment in India, patient perspectives of the DPS should be explored.…”
Section: Discussionsupporting
confidence: 82%
“…Previous pilot data from individuals with TB using ingestible sensor systems for ATT in the United States demonstrate high patient acceptance of the system and a desire to remain on DPS-based ATT adherence monitoring compared to DOT [ 16 ]. These sentiments mirror our previous work in HIV pre-exposure chemoprophylaxis that demonstrates high patient acceptance of these systems [ 24 26 ]. We anticipate that prior to deployment in India, patient perspectives of the DPS should be explored.…”
Section: Discussionsupporting
confidence: 82%
“…Our data currently represent one of the largest and most detailed study available on UX in persons with any medical diagnosis who have experience using an IS medication adherence system. Our findings are in line with those of Chai et al [56], who reported from qualitative interviews that 15 out of 90 persons using a digital pill system (DPS) [2] for PrEP adherence measurement perceived the device as acceptable, novel, and valuable. Interestingly, men who have sex with men (MSM) taking PrEP who reported substance use were also found to have positive perceptions toward using the DPS in the future [57].…”
Section: Principal Findingssupporting
confidence: 92%
“…Significant differences were observed between questionnaire nonrespondents and respondents, limiting the generalizability of our findings to persons taking PrEP who are homeless or use methamphetamine. In the latter regard, it is notable that Chai et al [56,57] report positive UX and attitude findings regarding DPS technology in MSM taking PrEP who use substances. Despite being one of the largest detailed study available on UX in persons who used an IS medication adherence system, our sample size was limited, and as the probability of reporting a positive experience was observed in >75% of the study population, the likelihood of identifying "current and future use personas" across our study was restricted by our sample size.…”
Section: Limitationsmentioning
confidence: 99%
“…Such conversations should carefully consider the intersection of race, ethnicity, and existing levels of medical mistrust on users’ perceptions of the DPS and ancillary systems [ 27 ]. Our previous work suggests that the use of these monitoring technologies may, in fact, increase one’s sense of personal accountability for their PrEP adherence, as well as improve relationships with medical providers by providing objective data around PrEP ingestions, and the context in which they occur, to long-term primary care and sexual health services [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous qualitative work demonstrated that MSM with substance use are accepting of DPS technology, willing to operate it in the real world to measure PrEP adherence, and perceive value in having on-demand access to PrEP adherence data [ 8 , 10 ]. Additionally, a recent study surveyed a national sample of MSM on PrEP who use substances to understand broader perceptions of the DPS and willingness to interact with the system for PrEP adherence measurement [ 11 ].…”
Section: Introductionmentioning
confidence: 99%